(untitled) (The Journal of Geography Education in Africa, 2020)
As Geographic Information Systems (GIS) have only been included in the curriculum in the last decade, many educators globally struggle to integrate GIS practice into their teaching strategies. Following the global trend, South African educators might feel ill-equipped as they did not receive formal GIS training in a higher education institution. This paper highlights key global and South African challenges regarding GIS integration. To compare the challenges that South Africa faces with those experienced elsewhere, this mixed-method study gleaned data from student educators (n=78) who completed a questionnaire regarding their GIS FET Phase education, followed by in-depth interviews with FET Phase educators (n=10) and two provincial heads of Geography for the Department of Basic Education (DBE). Results from this study indicate a clear global and national pattern of barrier categories.